Fructose potentiates the protective efficiency of live Edwardsiella tarda cell vaccine - Wang, Chao; Peng, Xuan-xian; Li, Hui (Frontiers in Immunology, 2023)
Vaccination is an effective measure to prevent infection by pathogens. Live vaccines have higher protective efficacy than inactivated vaccines. However, how live vaccines interact with the host from a metabolic perspective is unknown. The present study aimed to explore whether a live Edwardsiella tarda vaccine regulates host metabolism and whether this regulation is related to the protective efficacy of the vaccine. Therefore, a gas chromatography mass spectrometry (GC-MS)-based metabolomics approach was used to investigate the metabolomic profile of mice serum after vaccination with live E. tarda vaccine. Fructose was identified as a key biomarker that contributes to the immune protection induced by the live vaccine. Moreover, co-administration of exogenous fructose and the live vaccine synergistically promoted survival among mice and fish after bacterial challenge. These results indicate that metabolites, especially fructose, can potentiate the live E. tarda vaccine to increase its protective efficiency.